Role conflict and role ambiguity in information systems design - Ho, Ching Mei (2014)
Information systems (I.S.) technology is widely used in today’s business environment. Firms implement I.S. to improve productivity so as to gain a competitive edge. Unfortunately, some I.S. projects fail to achieve this purpose as users of these systems suffer stress and are dissatisfied with the systems. The failure of I.S. projects is due to systems designers not being fully aware of the social consequences of I.S. design and implementation. They pay insufficient attention to the social and behavioural factors in I.S. design.